Bioanalysis Young Investigator: Filippos Michopoulos. (September 2011) - Michopoulos, Filippos; Theodoridis, Georgios
Supervisor''s supporting comments It is my great pleasure to nominate Filippos Michopoulos for the Bioanalysis Young Investigator Award 2011. Filippos studied chemistry at the Aristotle University Thessaloniki (Greece), where his interest in life sciences led him to conduct a research study on multiple solid-phase microextraction. He then moved to Leiden University for an Erasmus stay where he was introduced to plant metabolomics by Robert Verpoorte. His MSc on Analytical Chemistry was on the study of extraction methods prior to LC–MS metabolomics. He immediately enrolled for a PhD, still under my supervision, on the discovery of biomarkers for arthritis. The last years Filippos spent several months in AstraZeneca UK working with my close collaborator Ian Wilson. Filippos'' priority is to excel in his research. He has a strong drive towards high-quality research. In the in state-of-the-art laboratories at Alderley Park he worked with cutting-edge technologies reaching a remarkable publication record: at present two papers published in high-ranked journals (including the Journal of Proteome Research, Molecular Biosystems and others) and several presentations at conferences and meetings. Filippos has a brilliant career lying ahead. I believe that such an award will help him a lot in promoting his vision.